1990
DOI: 10.1103/physrevlett.65.2712
|View full text |Cite
|
Sign up to set email alerts
|

Observation of phonon softening at the superconducting transition inBi2Sr2

Abstract: Resonant neutron absorption spectroscopy has been used to determine the temperature dependence of the average kinetic energy <£) of the Cu in Bi2Sr2CaCu2C>8 for the directions along and perpendicular to the c axis. (E) is directly related to the Cu phonon density of states and shows essentially normal behavior as a function of temperature for the c-axis direction. However, a sudden drop in (E) is observed at the superconducting transition for the motions in the Cu-O planes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(27 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…Earlier measurements using neutron resonance absorption spectroscopy (NRAS) had shown that the Cu a-b plane modes displayed an anomalous softening at a temperature slightly higher than the superconducting transition for Bi2Sr2CaCU208. [7] The There is a region centered around 25 meV where large parasitic scattering from the (0,0,6) reflection makes measurements impossible with the crystal orientation used.…”
Section: Previous Polarized Measurements[3] Havementioning
confidence: 99%
“…Earlier measurements using neutron resonance absorption spectroscopy (NRAS) had shown that the Cu a-b plane modes displayed an anomalous softening at a temperature slightly higher than the superconducting transition for Bi2Sr2CaCU208. [7] The There is a region centered around 25 meV where large parasitic scattering from the (0,0,6) reflection makes measurements impossible with the crystal orientation used.…”
Section: Previous Polarized Measurements[3] Havementioning
confidence: 99%
“…Furthermore, neutron resonance absorption spectroscopy measurements showed an anomalous decrease in the momentum of the Cu atoms in the a-b plane of Bi 2 Sr 2 CaCu 2 O 8 , 16 but there was no evidence for such anomalies in YBCO. 17 We have therefore used high quality crystalline c-oriented thin films for a more detailed investigation of this controversy.…”
mentioning
confidence: 99%
“…By using a beam energy of 3.1 MeV, which is slightly higher than the 3.045 MeV 16 O͑␣,␣͒ 16 O resonance energy, we could excite the 40 keV wide resonance for oxygen atoms in the middle region of the film. It was important to keep the beam energy constant and avoid ice buildup on the surface in order to probe the same depth region at each temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of superconductivity seems to freeze the dynamics of the lattice into a coherent state. Ion channeling experiments [7] and resonant neutron scattering [8] show that upon reducing the temperature below T, the atomic displacements become correlated and the thermal vibrational amplitude of the individual atoms decreases abruptly at T,. EXAFS measurements show strong dynamical fluctuations of certain intramolecular distances in the vicinity of T, [9,10].…”
Section: Introductionmentioning
confidence: 99%